2020
DOI: 10.1177/1477750920930375
|View full text |Cite
|
Sign up to set email alerts
|

Do moral development levels of the nurses affect their ethical decision making? A descriptive correlational study

Abstract: Background In the globalizing world, nurses often meet humans from different cultures and values. This fact has led them to make ethical decisions, which do not comply with their own moral jurisdictions at care setting. Objectives The objective of the study was to investigate the relationships between moral development levels of the nurses and their scores of nursing principled thinking and practical consideration during decision making for ethical dilemmas. Methods This was a descriptive correlational study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
2
6
0
3
Order By: Relevance
“…Most nurses who participated in this study were at the post-conventional level of moral development. This is similar to the findings of other studies, indicating that most Iranian nurses ( 28 ), Turkish nurses ( 29 ) and American nurses ( 30 ) were in the post-conventional level of moral development. However, the result of a meta-analysis showed that only expert nurses were at the post-conventional level, and that most nurses followed a uniform pattern of conventional ethical reasoning and practice ( 31 ).…”
Section: Discussionsupporting
confidence: 91%
“…Most nurses who participated in this study were at the post-conventional level of moral development. This is similar to the findings of other studies, indicating that most Iranian nurses ( 28 ), Turkish nurses ( 29 ) and American nurses ( 30 ) were in the post-conventional level of moral development. However, the result of a meta-analysis showed that only expert nurses were at the post-conventional level, and that most nurses followed a uniform pattern of conventional ethical reasoning and practice ( 31 ).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, familiarity scores of the majority nurses indicated that they were familiar with ethical dilemmas. Familiarity of the nurses with ethical dilemmas is considered to affect their decision making for ethical problems positively [34,42]. However, ethical decision-making of the nurses may be affected by the several factors such as policies and expectations of the institutions where they work, feeling of mastery of the medical profession, stressful environment, patient complex conditions, and the communication with patients that instead of following the rules, they listen to their inner voice [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as Arslan et al . 12 defend, this a global world, and nurses “often meet humans from different cultures and values”. The communication is one of the most effective weapons of nurses.…”
Section: Discussionmentioning
confidence: 99%